Analisis Pengaruh Belanja Bantuan sosial, Pendidikan dan Tingkat Pengangguran Terhadap Kemiskinan di Provinsi Jawa Timur Tahun 2018 - Dyah Puspitaning Ayu; prayudi setiawan prabowo (Universitas Negeri Surabaya, 2021)
The purpose of this study is to determine the effect of spending on social assistance,education and unemployment on poverty in East Java in 2018.This study uses crosssectionaldata analysis techniques of 38 districts/towns obtained from the Central Bureauof Statistics and then processed with multiple linear regression. The results of the studyshow that partially spending on social assistance had a significant positive effect onpoverty in East Java province in 2018, education had a significant negative impact onpoverty in East Java in 2018, and the unemployment rate did not significantly affectpoverty in East Java in 2018. Meanwhile, spending on social aid and educationsimultaneously affected poverty in East Java province in 2018. Keywords: education, poverty, sosial insurrence, unemployment